Development of Highly Sensitive Immunosensor for Detection of Staphylococcus aureus Based on AuPdPt Trimetallic Nanoparticles Functionalized Nanocomposite - Han, En (Micromachines (Basel), 2021)
The rapid and sensitive detection of Staphylococcus aureus (S. aureus) is essential to ensure food safety and protect humans from foodborne diseases. In this study, a sensitive and facile electrochemical immunosensor using AuPdPt trimetallic nanoparticles functionalized multi-walled carbon nanotubes (MWCNTs-AuPdPt) as the signal amplification platform was designed for the label-free detection of S. aureus. The nanocomposite of MWCNTs-AuPdPt was prepared by an in situ growth method of loading AuPdPt trimetallic nanoparticles on the surface of MWCNTs. The synthesized MWCNTs-AuPdPt featured good conductivity and superior catalytic performance for hydrogen peroxide. The nanocomposite of MWCNTs-AuPdPt with good biocompatibility and high specific surface area was further functionalized by anti-S. aureus antibodies. The immobilized antibodies could efficiently capture S. aureus to the modified electrode by an immune reaction, which resulted in the change of catalytic current intensity to realize the sensitive detection of S. aureus. The designed immunosensor could detect S. aureus in a linear range from 1.1 × 10(2) to 1.1 × 10(7) CFU mL(−1) with a low detection limit of 39 CFU mL(−1). Additionally, the proposed immunosensor was successfully applied to determine S. aureus in actual samples with acceptable results. This strategy provided a promising platform for highly sensitive determination of S. aureus and other pathogens in food products.